Efficacy of Paracetamol Compared to Ibuprofen on Closure of Patent Ductus Arteriosus in Premature Infants - Alviolita P. Rondonuwu; Johnny L. Rompis; David S. Waworuntu (Universitas Sam Ratulangi, 2022)
Abstract: Patent ductus arteriosus (PDA) is a congenital heart disease caused by failure of the ductus arteriosus to close immediately after birth. PDA can cause hemodynamic disturbances in premature infants as well as increased morbidity and mortality. Therefore, it needs to be closed immediately. Closuring of the PDA can use ibuprofen as a cyclooxygenase (COX) inhibitor, however, there are potential side effects. Paracetamol can be used as an alternative that acts as a peroxidase (POX) inhibitor with few side effects. This study aimed to compare the efficacy of paracetamol and ibuprofen on PDA closure in premature infants. This was a literature review, using four databases, such as Pubmed, ClinicalKey, Cochrane and ScienceDirect. The keywords used were paracetamol AND ibuprofen AND patent ductus arteriosus AND preterm AND newborn. Selection with inclusion and exclusion criteria obtained 13 articles. Paracetamol was as effective as ibuprofen for PDA closure therapy in premature infants. Paracetamol was safer than ibuprofen due to ibuprofenâ€™s side effects. In conclusion, paracetamol is as effective as ibuprofen and is safer to be used in PDA closure therapy in premature babies.Keywords: paracetamol; ibuprofen; patent ductus arteriosus; preterm; newbornÂ Abstrak: Patent ductus arteriosus (PDA) adalah penyakit jantung kongenital akibat gagalnya ductus arteriosus untuk menutup segera setelah lahir. PDA dapat menyebabkan gangguan hemodinamika pada bayi prematur, serta meningkatkan morbiditas dan mortalitas sehingga perlu segera ditutup. Penutupan PDA dapat menggunakan ibuprofen sebagai penghambat cyclo oxygenase (COX), namun terdapat efek samping potensial yang ditimbulkan. Parasetamol dapat digunakan sebagai alternatif yang bekerja menghambat peroksidase (POX) dengan sedikit efek samping. Penelitian ini bertujuan untuk membandingkan efikasi parasetamol dan ibuprofen untuk penutupan PDA pada bayi prematur. Penelitian ini berbentuk literature review, menggunakan empat database yaitu Pubmed, ClinicalKey, Cochrane dan ScienceDirect. Kata kunci yang digunakan yaitu paracetamol AND ibuprofen AND patent ductus arteriosus AND preterm AND newborn. Hasil seleksi dengan kriteria inklusi dan eksklusi mendapatkan 13 literatur. Hasil penelitian mendapatkan bahwa parasetamol sama efektif dengan ibuprofen untuk terapi penutupan PDA pada bayi prematur. Parasetamol lebih aman dibandingkan ibuprofen akibat efek samping yang ditimbulkan. Simpulan penelitian ini ialah parasetamol sama efektif dengan ibuprofen serta lebih aman untuk digunakan sebagai terapi penutupan PDA pada bayi prematur.Kata kunci: parasetamol; ibuprofen; patent ductus arteriosus; prematur; bayi